PENGEMBANGAN PEMBELAJARAN MATERI QUR’AN HADITS INTEGRATIF-INKLUSIF DI MADRASAH ALIYAH - Syaefudin Achmad (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2019)
One of the factors that determine the achievement of educational goals is learning. The Good learning can have a positive influence on students. Among the learning models that can be an alternative are learning based on an integrative-inclusive approach. The purpose of this learning model is so that students are able to integrate religious material with science, and have an inclusive, moderate, tolerant, and respectful personality among others. This goal is very important because Indonesia is an ocean of diverse ethnicity, language, customs, and religion. Learning through an intensive, inclusive approach can be done in Qur'an Hadiths at Madrasah Aliyah (MA). The Qur'an Hadith is an important subject because it deals with the source of Islam. In addition, students in Madrasah Aliyah (MA) have started to think critically, and are able to be brought into integrative-inclusive learning models. Keyword: Learning, Integrative-Inclusive, Qur'an Hadiths